2003
DOI: 10.1097/01.ccm.0000060867.17556.a0
|View full text |Cite
|
Sign up to set email alerts
|

Development of ionized hypomagnesemia is associated with higher mortality rates

Abstract: Development of ionized hypomagnesemia during an ICU stay is associated with a worse prognosis. It is often associated with the use of diuretics and the development of sepsis. Monitoring of ionized magnesium levels may have prognostic, and perhaps therapeutic, implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
126
1
9

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(145 citation statements)
references
References 42 publications
9
126
1
9
Order By: Relevance
“…Salem et al 25 observed that progressive magnesium deficiency and hypomagnesemia are strongly associated with increased mortality in experimental sepsis and magnesium replacement provides significant protection against endotoxin challenge. Sepsis is an independent risk factor for developing hypomagnesemia during ICU stay as observed by Soliman et al 17 In our study we found that the incidence of sepsis was much more common in patients with low magnesium in compared to normal magnesium (p value ). CS Limaye et al 20 also observed increased association of sepsis as twice as common in hypomagnesaemic patients.In our study hypomagnesemia was more common in diabetic patients (p value).…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Salem et al 25 observed that progressive magnesium deficiency and hypomagnesemia are strongly associated with increased mortality in experimental sepsis and magnesium replacement provides significant protection against endotoxin challenge. Sepsis is an independent risk factor for developing hypomagnesemia during ICU stay as observed by Soliman et al 17 In our study we found that the incidence of sepsis was much more common in patients with low magnesium in compared to normal magnesium (p value ). CS Limaye et al 20 also observed increased association of sepsis as twice as common in hypomagnesaemic patients.In our study hypomagnesemia was more common in diabetic patients (p value).…”
Section: Discussionsupporting
confidence: 69%
“…Chernow et al 8 ( 41% vs 13%), Rubiez et al 14 (46% vs 25%), and Safavi et al 18 (55% vs 35%) had found higher mortality whereas Guerin et al 9 (18% vs 17%) had found no difference in mortality between hypomagnesaemic and normomagnesemic patients in their studies.The higher mortality in hypomagnesaemic patients can be explained by increased association of morbidities like more need and longer duration of ventilatory assistance, association of sepsis and diabetes, other electrolyte abnormalities like hypocalcemia and hypokalemia in compared to patients with normal magnesium levels.The length of ICU stay and total hospital duration both were longer in hypomagnesaemic patients. Soliman et al 17 also observed longer duration of ICU stay in patients with low magnesium. They also found the length of ICU stay as an independent risk factor for hypomagnesemia development.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…İntra venöz uygulamalarında yüksek serum seviyeleri iyi tolere edilebilir. Yoğun bakıma yatışta kritik hastalıkla magnesyum seviyelerinde düşüş sıklığı ve bu faktörün olumsuz klinik sonuçla ilişkisi bir çok araştırmada gösterilmiştir (8)(9)(10). Çalışmamızın amacı yoğun bakım hastalarında hipomagnezeminin gerek yoğun bakıma girişte gerekse tedavi sırasında sıklıkla karşılaşılan bir durum olduğunu göstermek ve deliryum sıklığı ile ilişkisini araştırmaktır.…”
Section: Introductionunclassified